P o s t e r i o r r e v e r s i b l e e n c e p h a l o p a t h y syndrome : Case Report - Gupta, Dr. Vineetranjan; Mhaske, Dr. Sunil; Kothari, Dr. R. B.; Misal, Dr. Ganesh; Lonare, Dr. Nitin (VIMS Health Science Journal, 2017)
Posterior reversible encephalopathy syndrome (PRES) is a neurological syndrome. Posterior reversible encephalopathy syndrome also known as reversible posterior leukoencephalopathy syndrome presents with rapid onset of symptoms including headache, seizures, vomiting, altered consciousness, and visual disturbance. It is associated with hypertension. The clinical syndrome usually resolves within a week and the changes seen in magnetic resonance imaging resolve over days to weeks. The diagnosis is typically made clinically with magnetic resonance i m a g i n g o f t h e b r a i n o f t e n r e v e a l i n g hyperintensities on T2-weighed imaging. The treatment of Posterior reversible encephalopathy syndrome dependent on its cause. Anti-epileptic medication may also be appropriate.